Efecto de las microondas sobre la concentración de la caseína en la leche de vaca - Mejía Fustamante y Col., Karla del Rocío (2019)
The objective of this research is to determine the effect of microwaves on the concentration of casein in cow's milk for which it was used in a preliminary way a protein stability test, then a protein recognition by the method of Biuret and subsequently a quantification of proteins at 25 °C by the Sorensen method obtaining 1,17 g of casein (2.065 %). Five samples of milk of 10ml were taken each to be subjected to the microwave with exposure times of 10 s, 20 s, 30 s, 60 s and 120 s. Measuring the temperature at the end of them, which They were 29 °C, 35 °C, 44 °C, 52 °C and 77 °C. At the end of the exposure of the milk to the microwave, three aliquots of ten millilitres were taken of each of the samples to determine the percentage and amount of total casein using the Sorensen-Walker method followed by a casein isolation using an acid-base titration and addition of 1M acetic acid, concluding that the Total casein concentration in cow's milk is affected with the increase temperature inside the microwave, from a concentration of 2.065 % to 0.761 % of casein, affecting its nutritional value.